Association of Light-Intensity Physical Activity With Mortality in the Older Population: A Nationwide Cohort Study - Kim, Juntae; Yang, Pil-Sung; Park, Byoung-Eun; Kang, Tae Soo; Lim, Seong-Hoon; Cho, Sungsoo; Lee, Su-Yeon; Chung, Young Hak; Lee, Myung-Yong; Kim, Dongmin; Joung, Boyoung (Frontiers in Cardiovascular Medicine, 2022)
Background: There is a paucity of information about mortality related to light-intensity physical activity (LPA) in the older population. We examine the associations between physical activity and mortality, focusing on the effect of light-intensity physical activity and the dose-response relationship between physical activity and mortality. Methods: We analyzed a total of 58,537 participants aged ≥65 years (mean age, 73.9 ± 5.8 years; male, 36.0%) in the Korean National Health Insurance Service database between 2009 and 2012. The Date of the end of follow-up was December 31, 2013. Individuals were divided into 4 categories according to physical activity intensity: totally sedentary (43.3%), LPA only (35.8%), LPA and moderate- to vigorous-intensity physical activity (MVPA) (16.3%), MVPA only (4.5%). Physical activity was quantified using standardized self-reported questionnaires which composed of the duration and frequency of physical activity. Results: During a mean follow-up of 39.6 ± 14.0 months, 5,651 (9.7%) deaths occurred. Compared with totally sedentary individuals, those in the LPA only, LPA and MVPA, and MVPA only groups showed 26% (hazard ratio [HR] 0.74, 95% confidence interval [CI] 0.68–0.82), 27% (HR 0.73, 95% CI 0.63–0.84), and 34% (HR 0.66, 95% CI 0.54–0.79) lower all-cause mortality risk, showing an inverse relationship between physical activity intensity and mortality risk. In contrast, the LPA only, LPA and MVPA, and MVPA only groups represented a stronger inverse association with CV mortality (LPA: HR 0.76, 95% CI 0.62–0.92; LPA with MVPA: HR 0.74, 95% CI 0.55–0.999; MVPA, HR 0.57, 95% CI 0.37–0.87). Among participants performing LPA alone, participants performing less than the recommended dose of physical activity had lower all-cause mortality than those with sedentary activity (1–249 MET-min/week: HR 0.74, 95% CI 0.67–0.82, 250–499 MET-min/week: HR 0.65, 95% CI 0.59–0.72). Conclusion: Physical activity, even low doses of LPA, was associated with reduced mortality risk in the elderly population. This study may motivate sedentary individuals to engage in any physical activity for mortality benefits.